Foreign bodies in aero-digestive tract in children: spectrum of presentation and management - Patil, Rajashekhar T.; Prakash, Advait (International Surgery Journal, 2017)
Background: Foreign body (FB) ingestion and aspiration is quite common in children. It can be a life-threatening condition. Early diagnosis of foreign body aspiration is essential as delay in its recognition and treatment results in high morbidity and mortality. Symptoms seem to mostly depend on the anatomical location. The absence of specific symptoms indicating the occurrence of FB injury can lead to delay in diagnosis, thereby increasing the risk of complications. Methods: This is a prospective study which comprised of 50 patients with between 8 months and 4.5 years. FB involving different parts of the aero-digestive tract were included in the study. The site, side, symptoms and radiographic findings were recorded for each patient. Different procedures were used for retrieval of various FB at different locations. Majority of these procedures were performed under anaesthesia. Results: Most of the FB were organic in nature. Right side bronchus was more commonly involved. A combination of different procedures was used according to the site involved. All the FB were removed successfully and smoothly. There was minimum morbidity with no mortality and the overall outcome was excellent. Hospital stay varied according to the site of involvement. Conclusions: The symptoms of FB change with the site involved and many patients are even asymptomatic. A differential diagnosis of foreign body should always be made in an acute or chronic presentation of respiratory cases. Aspiration of foreign body should be suspected in all cases of broncho-pulmonary infection with atypical course. High index of suspicion is the cornerstone of diagnosis. Bronchoscopy is the best diagnostic and therapeutic method in all suspicions of foreign body of tracheo-bronchial tree. Proper and timely intervention optimizes the outcome.